(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تعد السياحة محرك نجاح للعديد من اقتصاديات الدول من حيث مساهمتها في التنمية الاقتصادية والاجتماعية، وفي تأمين فرص العمل وزيادتها، الموارد الحكومية وغير ذلك. وعلى النحو نفسه يمكن أن تكون السياحة الريفية محركاً بالنسبة إلى العديد من الاقتصاديات الريفية، من خلال مساهمة هذه السياحة في دفع الاقتصاد في المناطق الريفية، وفي تعزيز مستويات المعيشة وتحقيق التنمية الاقتصادية والاجتماعية وتمكين المرأة والحد من الهجرة الريفية، وهي مشاكل تعاني منها المناطق الريفية حول العالم، وإن كانت حدة هذه المشاكل تختلف من دولة إلى أخرى تبعاً لدرجة تطور هذه الدولة، ولكن بالمجمل تبقى هذه المشاكل السمة العامة للأرياف. لذلك فإنه بالنسبة إلى سورية، حيث نصيب المناطق الريفية من خطط التنمية ضعيف، ولا تزال تعاني فيها العديد من هذه المناطق مشاكل اقتصادية واجتماعية وتنموية، فإنه من المحتمل أن يكون للسياحة دور فعال في حل مشاكل الريف السوري نظراً لمساهمتها في حل كثير من المشاكل الاقتصادية و الاجتماعيّة كالهجرة من الريف إلى المدينة وتمكين المرأة. Tourism plays a key role in many countries in terms of its contribution to the economic and social development, the creation of more job opportunities and the increase in government resources and so forth. Similarly, rural tourism can be a driving force for many rural economies through its contribution in boosting the economy in rural areas, improving living standards, achieving economic and social development, empowerment of women and the reduction of rural migration, which comprise the main problems afflicting these areas around the world. The severity of these problems varies from one country to another according to the degree of development in this country, as they form a general characteristic of the countryside. This has driven various countries around the world to encourage non-agricultural activities, mainly tourism, hoping to improve the status of rural areas. In Syria, where the share of rural areas of development plans is weak, and they are still suffering from many developments, economic and social problems, tourism are likely to have an active role in solving the problems of rural Syria because of its contribution to solving many of economic and social problems such as migration from the countryside to the city and the empowerment of women.